2010
DOI: 10.1111/j.1540-8159.2010.02895.x
|View full text |Cite
|
Sign up to set email alerts
|

Greater Three‐Dimensional Ventricular Lead Tip Separation is Associated with Improved Outcome after Cardiac Resynchronization Therapy

Abstract: Greater three-dimensional separation of LV-to-RV leads is associated with improved response to CRT. A prospective multicenter trial is needed to assess lead separation as a predictor for response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
(33 reference statements)
1
12
0
Order By: Relevance
“…25,53,54,57,64,71 There were no differences between sexes on improvement in NYHA class. Regarding LVESV, women did, however, have an overall higher proportion of LVESV reduction (risk ratio = 1.12 [95% CI: 0.99-1.26]) (Fig.…”
Section: Effectiveness Outcomesmentioning
confidence: 76%
“…25,53,54,57,64,71 There were no differences between sexes on improvement in NYHA class. Regarding LVESV, women did, however, have an overall higher proportion of LVESV reduction (risk ratio = 1.12 [95% CI: 0.99-1.26]) (Fig.…”
Section: Effectiveness Outcomesmentioning
confidence: 76%
“…For example, wider LVright ventricular lead separation has been shown to provide better results. 50 A subanalysis of MADIT-CRT (Multicenter Automatic Defibrillator Implantation Trial with Cardiac Resynchronization Therapy) 20 showed that an apical LV lead position, as compared with a basal or midventricular position, resulted in a significant increased risk for HF or death. 51 Clinical trials of resynchronization included mainly patients in sinus rhythm.…”
mentioning
confidence: 99%
“…For example, wider LV-right ventricular lead separation has been shown to provide better results. 577 A subanalysis of MADIT-CRT (Multicenter Automatic Defibrillator Implantation Trial with Cardiac Resynchronization Therapy) 546 showed that an apical LV lead position, as compared with a basal or midventricular position, resulted in a significant increased risk for HF or death. 578 Clinical trials of resynchronization included mainly patients in sinus rhythm.…”
Section: Cardiac Resynchronization Therapy (Updated)mentioning
confidence: 99%